A scoping review on social problem-solving interventions for college students - Weiyi, Wang; Ma’rof, Aini Marina; Burhanuddin, Nur Aimi Nasuha (Frontiers in Education, 2025)
Social problem-solving is a critical skill that enables individuals to effectively cope with real-life challenges. For college students, enhancing this ability is essential for successful adaptation to post-graduation life. While previous reviews have primarily focused on improving social problem-solving skills in adolescents and younger students, or have examined its role in mental health disorders, few have systematically explored intervention programs specifically targeting college populations. This scoping review aimed to investigate the characteristics, underlying theoretical frameworks, and implementation strategies of social problem-solving training programs for college students. An extensive literature search was conducted in February 2024, followed by thematic analysis to synthesize the findings. Fourteen relevant studies were identified. Of these, eleven employed group-based training formats, while the remaining three involved a one-time induction, an online training module, and specialized training for nursing students conducted in a hospital unit. Most interventions were grounded in cognitive–behavioral and psychoeducational approaches. Thematic analysis revealed two primary dimensions: training format and training content. The training content generally emphasized knowledge acquisition, attitude development, and practical skills such as interpersonal communication and emotional regulation. These interventions, typically delivered over multiple sessions in team-based settings, were found to be effective in enhancing students’ social competence and problem-solving abilities.